Association between the catechol‐O‐methyltransferase polymorphism Val158Met and Alzheimer's disease in a Japanese population. (9th December 2014) - Shibata, Nobuto; Nagata, Tomoyuki; Tagai, Kenji; Shinagawa, Shunichiro; Ohnuma, Tohru; Kawai, Eri; Kasanuki, Koji; Shimazaki, Hiromi; Toda, Aiko; Tagata, Yuko; Nakada, Tomoko; Nakayama, Kazuhiko; et al.
<x xml:space="preserve">Abstract</x> Objective Catechol‐O‐methyltransferase (COMT) plays an important role in dopamine degradation, which is associated with the pathophysiology of Alzheimer's disease (AD) and alcoholism. A functional COMT polymorphism, Val158Met (rs4680 G > A), affects the onset of AD and is associated with alcohol dependence through dopamine receptor sensitivity in the prefrontal cortex. Methods The aim of this case–control study (398 cases and 149 controls) was to investigate whether Val158Met polymorphism influences the onset of AD stratified according to alcohol consumption and apolipoprotein E (APOE) status. We also used single photon‐emission computed tomography (SPECT) to analyse 26 patients with AD with the polymorphism. Results As a function of APOE status, the genotypic frequencies of rs4680 in patients with AD did not differ from those in controls. We detected a significant association between high alcohol consumption in patients with AD (HAC‐AD group) and the polymorphism in genotypic and allelic frequencies. Logistic regression analyses demonstrated that the presence of the APOE genotype with rs4680 increased the risk for HAC‐AD synergistically. Hyperperfusion in the right sub‐lobar insula of patients with the G/G genotype was found compared with that of patients with the G/A genotype. SPECT studies showed a relationship between the polymorphism and compensatory reactions for dysfunctions of dopaminergic neurotransmission in AD pathophysiology. Conclusion Although genetic association between the polymorphism and the onset of AD in a Japanese population were not observed, the polymorphism affected the risk for HAC‐AD. Copyright © 2014 John Wiley & Sons, Ltd.